2023
DOI: 10.1007/s11357-023-00802-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying systems thinking to unravel the mechanisms underlying orthostatic hypotension related fall risk

Abstract: Orthostatic hypotension (OH) is an established and common cardiovascular risk factor for falls. An in-depth understanding of the various interacting pathophysiological pathways contributing to OH-related falls is essential to guide improvements in diagnostic and treatment opportunities. We applied systems thinking to multidisciplinary map out causal mechanisms and risk factors. For this, we used group model building (GMB) to develop a causal loop diagram (CLD). The GMB was based on the input of experts from mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The problems with the use of betweenness- and closeness centrality to identify “structurally important nodes” 66 are far from unfamiliar, where many of the problems previously detected in other fields 61 also apply to CLDs and several papers applying network analysis metrics to CLDs also hint at potential limitations 8 , 23 , 24 , 26 , 28 , 36 38 , 42 , 52 . It has already been shown for different types of networks that betweenness- and closeness centrality do not provide reliable results over networks that differ slightly in structure, for example when a node is included or excluded 61 , 69 , 70 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The problems with the use of betweenness- and closeness centrality to identify “structurally important nodes” 66 are far from unfamiliar, where many of the problems previously detected in other fields 61 also apply to CLDs and several papers applying network analysis metrics to CLDs also hint at potential limitations 8 , 23 , 24 , 26 , 28 , 36 38 , 42 , 52 . It has already been shown for different types of networks that betweenness- and closeness centrality do not provide reliable results over networks that differ slightly in structure, for example when a node is included or excluded 61 , 69 , 70 .…”
Section: Discussionmentioning
confidence: 99%
“…In seeking alternative methods, network analysis 35 has gained momentum as an accepted practice to quantitatively identify leverage points based on CLDs 8 , 23 30 , 36 55 —for example in public health 24 , 38 , 45 , 50 , 52 , 53 , 55 . Here, 22 of the 29 papers that we identified that adopt this practice were published in 2021 (4 papers 23 , 25 , 37 , 50 ), 2022 (8 papers 27 , 28 , 43 45 , 47 , 49 , 52 ), and 2023 (10 papers to date 26 , 30 , 36 , 38 , 39 , 41 , 42 , 46 , 53 , 55 ). Network analysis seemingly has the potential to mathematically analyse a CLD, which in this context can be considered a network of factors, to systematically find which factors represent leverage points.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations